Towards an integrated understanding of the therapeutic utility of exclusive enteral nutrition in the treatment of Crohn's disease. Issue 4 (7th March 2016) - Ó Cuív, Páraic; Begun, Jakob; Keely, Simon; Lewindon, Peter J.; Morrison, Mark
Abstract : The therapeutic effects associated with EEN may be mediated by co-ordinate effects on the host gut mucosa and microbiota. Abstract : Crohn's disease (CD) is a chronic disease characterized by episodic and disabling inflammation of the gastrointestinal tract in genetically susceptible individuals. The incidence and prevalence of CD is rising rapidly across the world emphasising that disease risk is also influenced by environmental and lifestyle factors, as well as the microbial community resident in the gut. Childhood-onset CD is associated with an aggressive disease course that can adversely impact patient growth and development. There is no cure for CD however new onset and recurrent cases of paediatric CD are often responsive to exclusive enteral nutrition (EEN) treatment. EEN treatment involves the exclusive consumption of an elemental or polymeric formula for several weeks and it is well established as a primary intervention strategy. EEN treatments typically achieve remission rates of over 80% and importantly they are associated with a high rate of mucosal healing, far superior to steroids, which is prognostic of improved long-term health outcomes. Furthermore, they are safe, have few side effects, and improve nutritional status and linear growth. Surprisingly, despite the utility of EEN our understanding of the host-microbe-diet interactions that underpin clinical remission and mucosal healing are limited. Here, we review the current state of knowledge and propose that the induction of autophagy, in addition to modulation of the microbiota and coordinated effects on inflammation and epithelial cell biology, may be critical for the therapeutic effects associated with EEN. A better understanding of EEN treatment will provide new opportunities to restore gut homeostasis and prolong periods of remission, as well as provide new insights into the factors that trigger and perhaps prevent CD.